2014
DOI: 10.1021/np400722m
|View full text |Cite
|
Sign up to set email alerts
|

Cyanohydrin Phosphonate Natural Product from Streptomyces regensis

Abstract: Streptomyces regensis strain WC-3744 was identified as a potential phosphonic acid producer in a large-scale screen of microorganisms for the presence of the pepM gene, which encodes the key phosphonate biosynthetic enzyme phosphoenolpyruvate phosphonomutase. 31P NMR revealed the presence of several unidentified phosphonates in spent medium after growth of S. regensis. These compounds were purified and structurally characterized via extensive 1D and 2D NMR spectroscopic and mass spectrometric analyses. Three n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Two other bioactive strains, Streptomyces sp. NRRL S-474 and NRRL S-481, belong to a group of seven strains with a pepM gene cluster similar, but not identical, to the one found in Streptomyces regensis NRRL WC-3744, the known producer of hydroxynitrilaphos (40) (Fig. 3A).…”
Section: Dereplication Of Phosphonate Biosynthetic Pathways and Produmentioning
confidence: 93%
See 1 more Smart Citation
“…Two other bioactive strains, Streptomyces sp. NRRL S-474 and NRRL S-481, belong to a group of seven strains with a pepM gene cluster similar, but not identical, to the one found in Streptomyces regensis NRRL WC-3744, the known producer of hydroxynitrilaphos (40) (Fig. 3A).…”
Section: Dereplication Of Phosphonate Biosynthetic Pathways and Produmentioning
confidence: 93%
“…Including the eight additional molecules we recently reported elsewhere (24,38,40,45) (SI Appendix, Fig. S4), this program has yielded 19 new phosphonate natural products to date.…”
Section: Pepmentioning
confidence: 99%
“…NMR-guided fractionation was used in the isolation of three new compounds from S. regensis strain WC-3744 [9]. From this strain, N-acetyl-2AEP, N-acetyl-1-hydroxy-2AEP were purified along with cyanophos (cyano[hydroxyl]methyl phosphonic acid), a novel cyanohydrin compound.…”
Section: Recently Discovered Phosphonate Natural Productsmentioning
confidence: 99%
“…From this strain, N-acetyl-2AEP, N-acetyl-1-hydroxy-2AEP were purified along with cyanophos (cyano[hydroxyl]methyl phosphonic acid), a novel cyanohydrin compound. Analysis of the phosphonate gene clusters suggests that cyanophos may have origins from 2-AEP and is likely only an intermediate in the biosynthesis of a yet to be determined final product [9]. …”
Section: Recently Discovered Phosphonate Natural Productsmentioning
confidence: 99%
“…These studies demonstrated that enzymatic reactions could be studied in situ at low substrate concentrations without isotopic enrichment or purification. Other recent studies have employed 2D heteronuclear multiple bond correlation for the identification of C–P compounds and the elucidation of enzymatic activities …”
Section: Introductionmentioning
confidence: 99%